Dwarf emus from Baudin's voyage (1800–1804): an overlooked engraving by Nicolas Huet (1770–1830). Issue 2 (September 2022) - Fishburn, Matthew
Abstract : The French voyage of exploration to New Holland (Australia) between 1800 and 1804, commanded by Nicolas Baudin (1754–1803), made substantial natural history collections, notably capturing dwarf emus from the two distinct populations on King Island (Île King) in Bass Strait (December 1802) and Kangaroo Island (Île Decrès) (January 1803). Two of these emus survived their voyage to France, were housed briefly at the Empress Josephine's menagerie at Malmaison, and then the zoological park of the Jardin des Plantes in Paris. Both died in 1822. With the wild populations on both islands exterminated soon after Baudin's visit, two watercolours, one by Charles-Alexandre Lesueur (1778–1846) and one by Léon de Wailly ( fl . 1801–1824), have been central to the history of the dwarf emus. However, an important contemporary engraving by Nicolas Huet (1770–1830) depicting the two surviving emus in captivity has been overlooked. This essay explores the history of the images of the now extinct dwarf emus, as well as the production and significance of Huet's engraving.